MARKETING STRATEGIES FOR SMALL RETAIL BUSINESSES IN THE MIDST OF MARKETPLACE COMPETITION - Nuzuliati; Yanti Musyawarah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The development of digital marketplaces such as Shopee, Tokopedia, and TikTok Shop has posed serious challenges for small retail businesses, including in the city of Medan. This study aims to describe the marketing strategies applied by small retailers in the face of such competition. The approach used is descriptive qualitative with data collection techniques through in-depth interviews, observations, and documentation of five small retail stores in Medan. The results show that the most effective strategies include WhatsApp-based delivery services, social media utilization, customer loyalty programs, and local community approaches. Stores that implement adaptive strategies experience an increase in turnover of up to 35%, while stores that do not innovate tend to stagnate. Small retailers still have a competitive advantage in terms of emotional closeness, flexibility of service, and quick response to customers. This study concludes that the key to the success of small retail lies in the combination of a simple digital marketing strategy and a locality-based relational approach. Support from the government and the business community is urgently needed to improve digital literacy and the competitiveness of small retailers in the digital era.